First record of Odorrana liboensis Luo, Wang, Xiao, Wang & Zhou, 2021 (Amphibia: Anura: Ranidae) from Vietnam - Cuong, Pham The; Van Hoang, Chung; Ziegler, Thomas; Quang Nguyen, Truong (Academia Journal of Biology, 2025)
As a result of our fieldwork in Thai Nguyen and Lang Son provinces, we hereby record Odorrana liboensis Luo, Wang, Xiao, Wang & Zhou, 2021 for the first time from Vietnam. Morphologically, the newly collected specimens from Vietnam slightly differs from the type series from China by having a larger size (SVL 48.6–51.8 mm in males, SVL 61.4 mm in female vs. 47.1–49.9 mm in males, 55.8–58.2 mm in females) and by the absence of dorsolateral folds in adult females (vs. present). In terms of genetic divergence, the specimens from Vietnam differ from those from Guizhou province, China, by 0.14% to 0.70% based on the 16S rRNA fragment. Our finding increases the number of Odorrana species recorded in Vietnam to 24.